THE EFFECTS OF GONADECTOMY ON AGE- AND SEX- TYPICAL PATTERNS OF ETHANOL CONSUMPTION IN SPRAGUE-DAWLEY RATS - Vetter-O’Hagen, Courtney S. (2011)
BACKGROUND: Ethanol intake levels characteristic of adult males and females emerge post-pubertally. The present set of experiments examined the consequences of pre-pubertal and adult gonadectomies to explore whether the presence of gonadal hormones at puberty exerts organizational influences and/or plays an activational role in age- and sex-typical patterns of ethanol consumption. METHODS: Male and female Sprague-Dawley rats were gonadectomized (GX), received sham gonadectomy (SH) or were left non-manipulated (NM) at one of two ages, either pre-pubertally on postnatal day (P) 23 (early) or post-pubertally in adulthood on P70 (late). Early surgery animals were tested for ethanol consumption either during adolescence (P28-39) or in adulthood at the same age that late surgery animals were tested (P75-86). Voluntary ethanol consumption was indexed using a 2 hr limited-access paradigm, with access to two bottles: one containing water, and the other a sweetened ethanol solution. RESULTS: Age of GX did not impact patterns of ethanol consumption. Removal of testicular hormones in males, regardless of age of removal, elevated consumption levels in adulthood to female-typical levels. Ovariectomy did not have notable effects on ethanol drinking in females. Ethanol intake and preference of early SH males was significantly greater than that of both late SH and NM males. Removal of the gonads prior to puberty did not influence ethanol drinking or preference during adolescence in either males or females. CONCLUSIONS: These results suggest that testicular hormones play an activational role in lowering ethanol intake and preference of adult male rats. Pubertal hormones, in contrast, were found to exert little influence on ethanol drinking or preference during adolescence, although the effect of surgical manipulation itself during development was found to exert a long-lasting facilitatory effect on ethanol consumption in adulthood.